Changes in Pelagic Fisheries Composition in Relation to Climate Change: A Case Study of Prigi Waters, East Java - Yanida Azhari Julianinda; Feni Iranawati; Defri Yona; Zulfan Khaidar; Aida Sartimbul (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2026)
The variability of Sea Surface Temperature (SST) and chlorophyll-a distribution in the southern waters of East Java is heavily influenced by the Indian Ocean Dipole (IOD) phenomenon. This study examines oceanographic parameter variability, their relationship with the IOD from 2003 to 2014, and fishing dynamics in the southern waters of East Java, particularly at PPN Prigi. Data utilized include SST and chlorophyll-a from Aqua-MODIS satellites, the Dipole Mode Index (DMI), and 12 years of fish production records. The analysis reveals significant fluctuations in SST and chlorophyll-a, with a strong inverse relationship (correlation: –0.677), where chlorophyll-a concentrations rise as SST decreases. Positive IOD events reduce SST, while negative IOD events increase SST, with correlations of –0.591 for SST and IOD and 0.601 for chlorophyll-a and IOD. During the positive IOD events of 2006–2008, SST decreased, leading to increased fish production. Conversely, the negative IOD in 2010 raised SST, contributing to a decline in fish stocks. Over the 12-year period, a notable increase in Bali Sardinella and skipjack production was observed, despite a sharp decrease in 2010 caused by higher SST levels. This study highlights the importance of understanding the interactions between SST, chlorophyll-a, and IOD in developing sustainable fisheries management strategies. These insights can support efforts to optimize fish resource utilization, mitigate the impacts of climate variability, and ensure long-term fisheries productivity in the southern waters of East Java, particularly for strengthening adaptive resource planning within climate-sensitive pelagic ecosystems and supporting informed decision-making for regional fisheries policies and sustainable blue-growth initiatives.